MECHANISMS OF PUBLIC MANAGEMENT AND ADMINISTRATION IN THE SPHERE OF CIVIL PROTECTION IN FOREIGN COUNTRIES - Maystro , S. V.; Kropyvnytskyi , V. S (Theory and Practice of Public Administration, 2021)
The article describes the features of public management and administration in the sphere of civil protection in foreign countries. Mechanisms of public management and administration in the sphere of civil protection in foreign countries are considered. The differences and effectiveness of the existing systems of public management and administration in the sphere of civil protection in foreign countries are clarified. The problems and contradictions of the existing systems of public management and administration in the sphere of civil protection in foreign countries are identified. Suggestions are given regarding the directions and possibilities of adaptation in Ukraine of the world experience of public management and administration in the sphere of civil protection.The experience of public management of civil protection in the USA, Norway, Japan, Australia, Great Britain, and Canada is studied. Common to these countries in the sphere of public administration and civil protection administration is the effectiveness of emergency prevention, sufficient funding for civil protection authorities and rescue services, a high level of civil protection equipment and rescue equipment, an effective public alert system for natural disasters and emergencies, as well as effective cooperation between central government and local government.The analysis of public management of civil protection of such EU countries as Belgium, France, Italy, Spain, Germany, Austria, Poland, Lithuania, Latvia, Estonia, the Netherlands, Sweden, Switzerland is carried out. Research shows that in most European countries there are no separate agencies responsible for civil protection. These functions are provided by specialized structures, subordinated mainly to the Ministry of the Interior. At the level of local self-government, specialized civil protection structures cooperate with local self-government bodies and voluntary public organizations.The development of civil protection in foreign countries shows that public management of civil protection is aimed primarily at forecasting and preventing emergencies, analyzing possible scenarios for their development, as well as the organization of civil protection measures and rapid response to their occurrence.